Transformation of Radicalism Discourse into Extremist Violence (Analysis of News on the Handling of Radical Movements in Indonesia) - Sunardi Nardi Panjaitan (Jurnal Studi Sosial dan Politik, 2020)
Abstract This article explains how the transformation of the discourse of radicalism into extremist violence in media coverage. Radical movements tend to be interpreted as acts of violence. Not only that, the root of terrorism is caused by radicalism. But the discourse about radicalism continues to develop, the form of radical action or action is also the idea of ​​building an Islamic state. Therefore the state is important to deal with radical movements or radicalism understandings, especially through the media coverage. But in the media coverage, the state labeled Islamic groups as radical grups. The labeling is caused by the government not having an overall idea or concept towards acts of terrorism or radical movements. Proof of radicalism in Indonesia always moves between two pendulum. Action and regulation. When terror and violence occur, the government responds to these events by issuing a number of regulations and discourse several policies in the media. As a result, acts of terror tend to recur, and injustice and discrimination tend to be addressed to certain groups. Therefore, the transformation of radicalism into extremist violence as a response to the discourse on the handling of terrorism in Indonesia with overall concepts and ideas. Keyword: Radical Movement, Terrorism, media coverage, Extremist Violence